Genetics - Predisposition and Application to Primary Preventions of CAD - Roberts, M.D. MACC, Robert; Fair, B.S., Jacques; Murphy, B.S., Danyael; Roberts, MA, Alison MacKenna (International Journal of Innovative Research in Medical Science, 2021)
The risk of Coronary Artery Disease (CAD) has been recognized to be approximately 50% due to genetic predisposition and the remainder due to lifestyle and acquired causes. The first genetic risk variant was discovered in 2007 and since that time over 200 genetic risk variants predisposing to CAD have been discovered. These risk variants have been encrypted on to a microarray in preparation for their evaluation as a means to predict one’s risk for CAD. The Polygenic Risk Score (PRS) derived from these variants provides a single number for the total genetic risk burden. The PRS has been evaluated in several studies, totaling over 1 million individuals. Individuals categorized as high genetic risk for CAD based on PRS stratification show 2-3 fold increase risk for cardiac events. Retrospective analysis of several clinical trials showed lowering plasma LDL cholesterol is associated with decreased genetic risk and the frequency of cardiac events. A prospective study showed a favorable lifestyle to be associated with 47% reduction in the high genetic risk group and a similar reduction of 50% from physical activity in another prospective study. The PRS unlike acquired factors is not age-dependent but determined at conception and does not change throughout one’s lifetime. The several ethical, legal, and social implications associated with the clinical use of a PRS for CAD is fully discussed. The routine clinical application of the PRS for early primary prevention of CAD has the potential to be a paradigm shift in the prevention of this pandemic disease.